2017
DOI: 10.1097/sla.0000000000001692
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Postoperative Complications After Curative Resection for Patients With Esophageal Squamous Cell Carcinoma

Abstract: The development of postoperative complications is an independent disease-specific poor prognostic factor after curative resection for patients with less-advanced esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 24 publications
3
91
1
1
Order By: Relevance
“…Of note, Ito et al previously reported on a cohort of patients with colorectal liver metastasis and noted that morbidity was not an independent predictor of recurrence in the entire cohort, but was predictive of recurrence among patients with a low clinical risk score . Similarly, Saeki et al reported that patients with esophageal squamous cell cancer and early stage disease (pStages 0‐II) were more likely to be affected by postoperative complications versus patients with advanced‐stage disease (pStages III and IV) in terms of cancer progression …”
Section: Discussionmentioning
confidence: 99%
“…Of note, Ito et al previously reported on a cohort of patients with colorectal liver metastasis and noted that morbidity was not an independent predictor of recurrence in the entire cohort, but was predictive of recurrence among patients with a low clinical risk score . Similarly, Saeki et al reported that patients with esophageal squamous cell cancer and early stage disease (pStages 0‐II) were more likely to be affected by postoperative complications versus patients with advanced‐stage disease (pStages III and IV) in terms of cancer progression …”
Section: Discussionmentioning
confidence: 99%
“…The impact of postoperative complications on long‐term survival has been investigated for many cancers , . In some studies , a negative impact of complications following oesophagectomy on long‐term survival was reported. In other studies , , complications did not affect long‐term survival.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that operative volume, anastomotic location, tumor location/size, cardiopulmonary disease, renal disease, procedure type, ASA score, and diabetes may all be associated with anastomotic leak . A better understanding of characteristics contributing to the leak is critical, as research suggests patients who develop significant complications following esophagectomy have inferior survival outcomes and higher recurrence rates, even when adjusted for characteristics of the patient and disease . Moreover, anastomotic leaks are associated with prolonged hospital stays and higher perioperative morbidity and mortality rates .…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of characteristics contributing to the leak is critical, as research suggests patients who develop significant complications following esophagectomy have inferior survival outcomes and higher recurrence rates, even when adjusted for characteristics of the patient and disease . Moreover, anastomotic leaks are associated with prolonged hospital stays and higher perioperative morbidity and mortality rates . Identification of characteristics associated with anastomotic leak could permit risk stratification and implementation of targeted interventions to promote early detection and minimize downstream sequella.…”
Section: Introductionmentioning
confidence: 99%